Pretrial Dilemma and Main Case Examination - Erwin Ubwarin; Firel Sahetapy (Criminal of Law Department, Faculty of Law, Pattimura University, 2022)
The purpose of this paper is to discuss the interpretation of the limits of the pretrial process and the start of the examination of the main case examination, often causing debates between judges, prosecutors, legal advisors and the defendant. The research method used is normative juridical. The results of the study show that there are two contradictions between the Constitutional Court Number 102/PUU-XIII/2015 and the Supreme Court Circular Letter Number 5 of 2021, which both provide different explanations regarding Article 82 paragraph (1) letter d of the Criminal Procedure Code, The Supreme Court Circular does not protect the defendants human rights by taking into account the due process model principle, because when the public prosecutor submits a case to the court, it is considered that the suspect's rights in the judicial process are automatically invalidated. In fact, if seen in Article 143 paragraph (1) of the Criminal Procedure Code, the indictment is only a requirement for delegation, not reading the indictment at the time of the main case, and Article 79 and Article 80 clearly explain the protection of the rights of suspects and victims' rights in the pretrial process.